‘Cosmopolitan start-up’ capital: mobility and school choices of global middle class parents - Beech, Jason; Koh, Aaron; Maxwell, Claire; Yemini, Miri; Tucker, Khen; Barrenechea, Ignacio (Cambridge Journal of Education, 2021)
In this paper the authors study 19 Global Middle Class (GMC) families currently residing in four global cities: Hong Kong; London; Buenos Aires; and Tel Aviv. Through qualitative in-depth interviews, they sought to gather insights about GMC parenting strategies, specifically drawing attention to the decision-making processes of school choice. To facilitate their analysis, they draw on Bourdieu’s theory on types of capital and Ben-Porath’s notion of bounded rationality. From the inductive analysis of their interview data with mobile GMC parents, they identified a subtype of cultural capital they called ‘cosmopolitan start-up capital’. The overall argument in the paper is that the accumulation of cosmopolitan start-up capital is a specific strategy guiding the GMC families’ school choice practices, set within a frame of mobilities. Given the growing number of mobile families who continuously enter and exit local education systems, focusing on this group is pertinent for policy makers and practitioners around the world.
Publisher: Routledge _eprint: https://doi.org/10.1080/0305764X.2020.1863913
Keywords: Bourdieu; School choice; cosmopolitan start-up capital; global middle class (GMC); mobility